Interior Redesign of Kertajaya Intercity Bus Terminal, Mojokerto, Using A Cultural Approach - Firhan Rifqi Ramadzani; Dyan Agustin (Institut Teknologi Pendidikan Indonesia, 2026)
Bus terminals serve as land transportation hubs that not only facilitate passenger mobility but also function as public spaces that accommodate social interactions and community economic activities. As a Type B terminal, Kertajaya Terminal in Mojokerto holds a strategic role in supporting regional mobility. However, its current interior conditions still present several issues, including inadequate spatial comfort, poorly organized circulation patterns, and a lack of strong representation of local cultural identity within the spatial design. This study aims to redesign the interior of Kertajaya Terminal Mojokerto through a local cultural approach in order to create a terminal environment that is comfortable, functional, and possesses a distinctive character representing the identity of Mojokerto City. The research employs a qualitative design-based methodology using a case study approach. The design process is guided by the principles of Design Thinking, which include problem identification and data collection, idea generation and concept development, as well as design evaluation and selection. Data were collected through observations of existing conditions, interviews with terminal users and management, and literature reviews related to terminal interior design and the local culture of Mojokerto. The findings indicate that the application of a cultural approach through the integration of values, symbols, and visual elements inspired by Majapahit culture can enhance the quality of interior spaces both functionally and symbolically. The resulting redesign improves spatial comfort, circulation clarity, and the strengthening of the terminal’s visual identity. This study highlights that a cultural approach in terminal interior design can serve as an effective strategy for improving the quality of public transportation spaces while simultaneously reinforcing the image and identity of the city.